2022
DOI: 10.1002/eap.2504
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for geographic variation in species‐habitat associations during habitat suitability modeling

Abstract: Range‐wide species conservation efforts are facilitated by spatially explicit estimates of habitat suitability. However, species‐environment relationships often vary geographically and models assuming geographically constant relationships may result in misleading inferences. We present the first range‐wide habitat suitability model (HSM) for the federally threatened eastern indigo snake (Drymarchon couperi) as a case study illustrating an approach to account for known latitudinal variation in habitat associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Part of our predictor selection process included using a priori information from expertise and relevant literature [ 92 ]. Several predictors identified herein, e.g., maximum summer and minimum winter temperature, have worked well for SDMs of snakes in similar latitudes or regions, including congenerics and conspecifics [ 53 , 100 104 ]. Overall, our high performance evaluation scores suggest that our selected variables and ensemble modeling process adequately reflect aridland Thamnophis -environmental relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Part of our predictor selection process included using a priori information from expertise and relevant literature [ 92 ]. Several predictors identified herein, e.g., maximum summer and minimum winter temperature, have worked well for SDMs of snakes in similar latitudes or regions, including congenerics and conspecifics [ 53 , 100 104 ]. Overall, our high performance evaluation scores suggest that our selected variables and ensemble modeling process adequately reflect aridland Thamnophis -environmental relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the positive effect of AES on shrike occurrence probability diminished at high levels of structural landscape complexity (SHRUBS), though at varying degrees across regions. Differences in the environmental subniches among shrike populations may be the cause (Chandler et al 2022). The red-backed shrike is considered a farmland species throughout Europe, but has been shown to inhabit Relationships were graphed for each predictor with all other covariates held at their medians.…”
Section: Cross-regional Variability In Landscape-moderated Aes Effect...mentioning
confidence: 99%
“…1), excluding areas west of Mobile Bay, Alabama (e.g., southern Mississippi, Enge et al 2013; U. S. Fish and Wildlife Service 2019). The habitat suitability model we used was developed over the approximate contemporary distribution of DRCO in south-central and southeast Georgia and peninsular Florida as described in Chandler et al (2022). Our study area included a diversity of natural vegetation communities, including xeric sandhill and scrub, mesic pine flatwoods, hardwood hammocks, coastal hammocks and dunes, and forested and non-forested wetlands.…”
Section: Study Areamentioning
confidence: 99%
“…Furthermore, defining conservation units solely on genetic data may fail to prioritize local, yet important, populations (Taylor and Dizon 1999). Chandler et al (2022) published a range-wide multi-scale habitat suitability model for DRCO that accounts for known latitudinal differences in habitat associations (Hyslop et al 2014;, which could be used to define inter-connected habitat-based conservation units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation